Anonymity and Self-Expression in Online Rating Systems - An Experimental Analysis - Hoyer, Britta; van Straaten, Dirk (Journal of Behavioral and Experimental Economics)
Keywords: General Social Sciences; Economics and Econometrics; Applied Psychology

Behavioral Economics for Human-in-the-loop Control Systems Design: Overconfidence and the hot hand fallacy - Protte, Marius; Fahr, René; Quevedo, Daniel E. (IEEE Control Systems Magazine)
Successful design of human-in-the-loop control sys- tems requires appropriate models for human decision makers. Whilst most paradigms adopted in the control systems literature hide the (limited) decision capability of humans, in behavioral economics individual decision making and optimization processes are well-known to be affected by perceptual and behavioral biases. Our goal is to enrich control engineering with some insights from behavioral economics research through exposing such biases in control-relevant settings. This paper addresses the following two key questions: 1) How do behavioral biases affect decision making? 2) What is the role played by feedback in human-in-the-loop control systems? Our experimental framework shows how individuals behave when faced with the task of piloting an UAV under risk and uncertainty, paralleling a real-world decision-making scenario. Our findings support the notion of humans in Cyberphysical Systems underlying behavioral biases regardless of – or even because of – receiving immediate outcome feedback. We observe substantial shares of drone controllers to act inefficiently through either flying excessively (overconfident) or overly conservatively (underconfident). Furthermore, we observe human-controllers to self-servingly misinterpret random sequences through being subject to a “hot hand fallacy”. We advise control engineers to mind the human component in order not to compromise technological accomplishments through human issues.

Network Formation and Disruption - An Experiment: Are equilibrium networks too complex? - Endres, Angelika Elfriede; Recker, Sonja; Mir Djawadi, Behnud; Hoyer, Britta (Journal of Economic Behavior and Organization)
Models on network formation have often been extended to include the potential of network disruption in recent years. Whereas the theoretical research on network formation under the threat of disruption has thus gained prominence, hardly any experimental research exists so far. In this paper, we therefore experimentally study the emergence of networks including the aspect of a known external threat by relating theoretical predictions by Dzuibiński and Goyal (2013) to actual observed behaviour. We deal with the question if subjects in the role of a strategic Designer are able to form safe networks for least costs while facing a strategic Adversary who is going to attack their networks. Varying the costs for protecting nodes, we designed and tested two treatments with different predictions for the equilibrium network and investigated whether one of the least cost equilibrium networks was more likely to be reached. Furthermore, the influence of the subjects’ farsightedness on their decision-making process was elicited and analysed. We find that while subjects are able to build safe networks in both treatments, equilibrium networks are only built in one of the two treatments. In the other treatment, predominantly safe networks are built but they are not for least costs. Additionally, we find that farsightedness –as measured in our experiment– has no influence on whether subjects are able to build safe or least cost equilibrium networks. Two robustness settings with a reduced external threat or more liberties to modify the initial networks qualitatively confirm our results. Overall, in this experiment observed behaviour is only partially in line with the theoretical predictions by Dzuibiński and Goyal (2013).

Certiﬁcation Matters for Service Markets - Jakobs, Marie-Christine; Krämer, Julia; van Straaten, Dirk; Lettmann, Theodor (The Ninth International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
Whenever customers have to decide between different instances of the same product, they are interested in buying the best product. In contrast, companies are interested in reducing the construction effort (and usually as a consequence thereof, the quality) to gain profit. The described setting is widely known as opposed preferences in quality of the product and also applies to the context of service-oriented computing. In general, service-oriented computing emphasizes the construction of large software systems out of existing services, where services are small and self-contained pieces of software that adhere to a specified interface. Several implementations of the same interface are considered as several instances of the same service. Thereby, customers are interested in buying the best service implementation for their service composition wrt. to metrics, such as costs, energy, memory consumption, or execution time. One way to ensure the service quality is to employ certificates, which can come in different kinds: Technical certificates proving correctness can be automatically constructed by the service provider and again be automatically checked by the user. Digital certificates allow proof of the integrity of a product. Other certificates might be rolled out if service providers follow a good software construction principle, which is checked in annual audits. Whereas all of these certificates are handled differently in service markets, what they have in common is that they influence the buying decisions of customers. In this paper, we review state-of-the-art developments in certification with respect to service-oriented computing. We not only discuss how certificates are constructed and handled in service-oriented computing but also review the effects of certificates on the market from an economic perspective.

Asymmetric Dominance Effect with Multiple Decoys for Low- and High-Variance Lotteries - Sürücü, Oktay; Mir Djawadi, Behnud; Brangewitz, Sonja

Verantwortung macht Sinn: Corporate Social Responsibility - Fahr, René (Personnel Quarterly Vol. 4)

“…and they are really lying”: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment. - Fahr, Rene; Mir Djawadi, Behnud (Journal of Economic Psychology)
We investigate the pervasiveness of lying in professional contexts such as insurance fraud, tax evasion and untrue job applications. We argue that lying in professional contexts share three characterizing features: (1) the gain from the dishonest behavior is uncertain, (2) the harm that lying may cause to the other party is only indirect and (3) lies are more indirect lies by action or written statements. Conducted as a field experiment with a heterogenous group of participants during a University ‘‘Open House Day’’, our ‘‘gumball-machineexperiment’’ provides field evidence on how preferences for lying are shaped in situations typically found in professional contexts which we consider to be particularly prone to lying behavior compared to other contexts. As a key innovation, our experimental design allows measuring exact levels of cheating behavior under anonymous conditions. We find clean evidence that cheating is prevalent across all sub groups and that more than 32% of the population cheats for their own gain. However, an analysis of the cheating rates with respect to highest educational degree and professional status reveals that students cheat more than non-students. This finding warrants a careful interpretation of generalizing laboratory findings with student subjects about the prevalence of cheating in the population.

"...and they are really lying: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment" - Djawadi, Behnud Mir; Fahr, René (Journal of Economic Psychology)

Kleine Unternehmen - kleine Verantwortung? Theorie und Praxis unternehmerischer Verantwortung im Mittelstand - Fahr, Rene; Foit, Dörte (BWL im Mittelstand - Grundlagen-Besonderheiten-Entwicklungen")

Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change - Mir Djawadi, Behnud; Fahr, Rene; Turk, Florian (Value in Health)
BackgroundMedical nonpersistence is a worldwide problem of striking magnitude. Although many fields of studies including epidemiology, sociology, and psychology try to identify determinants for medical nonpersistence, comprehensive research to explain medical nonpersistence from an economics perspective is rather scarce.ObjectivesThe aim of the study was to develop a conceptual framework that augments standard economic choice theory with psychological concepts of behavioral economics to understand how patients’ preferences for discontinuing with therapy arise over the course of the medical treatment. The availability of such a framework allows the targeted design of mechanisms for intervention strategies.MethodsOur conceptual framework models the patient as an active economic agent who evaluates the benefits and costs for continuing with therapy. We argue that a combination of loss aversion and mental accounting operations explains why patients discontinue with therapy at a specific point in time. We designed a randomized laboratory economic experiment with a student subject pool to investigate the behavioral predictions.ResultsSubjects continue with therapy as long as experienced utility losses have to be compensated. As soon as previous losses are evened out, subjects perceive the marginal benefit of persistence lower than in the beginning of the treatment. Consequently, subjects start to discontinue with therapy.ConclusionsOur results highlight that concepts of behavioral economics capture the dynamic structure of medical nonpersistence better than does standard economic choice theory. We recommend that behavioral economics should be a mandatory part of the development of possible intervention strategies aimed at improving patients’ compliance and persistence behavior.